Co-encapsulation of curcumin and resveratrol in zein-bovine serum albumin nanoparticles using a pH-driven method. Issue 7 (10th March 2023) - Chen, Xiao; Yu, Chong; Zhang, Yi; Wu, Yan-Chao; Ma, Yao; Li, Hui-Jing
Abstract : In the present study, zein–bovine serum albumin (BSA) composite nanoparticles (NPs) are produced with the use of a pH-driven method. Abstract : In the present study, zein–bovine serum albumin (BSA) composite nanoparticles (NPs) are produced with the use of a pH-driven method. The mass ratio of BSA to zein has a significant impact on the particle size, but exhibits a limited effect on the surface charge. With an optimal zein/BSA weight ratio of 1 : 2, zein–BSA core–shell NPs are fabricated for the single/co-loading of curcumin and resveratrol. The incorporation of curcumin or/and resveratrol into zein–BSA NPs changes the configuration of the proteins (zein and BSA), and zein NPs transform resveratrol and curcumin from the crystalline structure to the amorphous state. Compared with resveratrol, curcumin has higher binding strength with zein BSA NPs, showing higher encapsulation efficiency and storage stability. The co-encapsulation of curcumin is found to be an effective method to improve the encapsulation efficiency and shelf-stability of resveratrol. Through this co-encapsulation technology, curcumin and resveratrol are retained in different NP regions via polarity mediation and released at different rates. The hybrid NPs formed from zein and BSA through a pH-driven method exhibit the potential of co-delivery of resveratrol and curcumin.